Forward modeling of P- and S-waves response of fractures intersected with horizontal wells in tight reservoirs - Fan, Huajun; Liu, Peng; Zhao, Hao; Zhang, Mengsheng; Liao, Maojie; Zhong, Guanghai; Wang, Kewen; Wu, Hongliang (Frontiers in Earth Science, 2023)
Horizontal wells play an important role in expanding the drilling volume of reservoirs and oil production area, and are widely used in unconventional reservoirs, especially in shale reservoirs. Fractures have a positive effect on reservoir permeability, but fractures can also cause accidents such as casing deformation and inter-well frac-hit. It is of great significance to identify and evaluate fractures intersected with horizontal wells in shale reservoirs. In this paper, a three-dimensional numerical model of horizontal wells and fractures in shale reservoirs is designed. The responses of monopole P-wave and dipole S-wave to fractures with different width, dip angle and filling medium are systematically studied, by using three-dimensional finite difference algorithm. The results show that when the fracture is filled with calcite, the amplitude attenuation of monopole P-wave and dipole S-wave has a monotonic exponential increase with the increase of fracture width and the decrease of fracture dip angle. In the real data processing, the amplitude attenuation of P- and S-waves can be used to jointly evaluate the fracture filled with calcite. When the fracture is filled with water, both P- and S-waves have prominent amplitude attenuation. P wave amplitude attenuation does not have a monotonic variation with the increase of fracture width but it has a monotonic increase with the decrease of fracture dip angle. S wave amplitude attenuation has a monotonic increase with the increase of fracture width and the decrease of fracture dip angle. The amplitude attenuation of P- and S- waves rises significantly when the fracture is filled with natural gas. This study is crucial for better understanding the response of P- and S-waves to fractures intersected with horizontal well in shale reservoirs, and it provides useful information for the inversion of fracture parameters by using P- and S-waves.